A subjetividade da pessoa surda na escrita do português como segunda língua: constituições, educação e surdez - LOBATO, Merian de Cristo (Universidade Federal do Pará, 2023)
The research entitled “The Subjectivity of Deaf Person in Writing Portuguese as Second Language: Constitutions, Education and Deafness”, presents the analysis of texts written by young deaf participants of the Project “Laboratory of Portuguese Language Teaching for the Deaf” that happened through the GEPEES Group. The objective of the project was to provide the deaf the development of the written language in Portuguese because to the great difficulty presented by them when writing. This difficulty was verified from the dialogues established with the deaf community from the other projects, as well evidenced from the first written record requested at the first moment of our meeting. The analysis of written texts provided this investigation that has as main objective: understand the subjectivity of deaf people through the production of senses and meanings that emerge from productions written in Portuguese as a second language, and as specific objectivies: to carry out theoretical reflection about the deaf education, about process of inclusion and on the debates around this theme; Discuss the issue of subjectivity and thus to guide the analysis of this research from the looking of written material, of elaboration process of this product called written production. As methodology, Vygotsky's cultural historical perspective (1983) used which, ally to with the studies of authors who focus on this subject and the assumptions of the ethnographic analysis, supported this research. The project that gave rise to this investigation was elaborated from interactionist approaches and pedagogical strategies, that started from the understanding of the deaf person as holder of cultural specificities, where activities mediated by sign language were developed. Thus, we conclude from the deaf written analysis that it presents the voices of subjectivities constituted in intersubjective relations in the socio, cultural and educational contexts, sometimes affirming the linguistic subjectivity acquired throughout life through sign language, sometimes presenting in the written materiality, the Portuguese Language from the recognition and linguistic relevance that this new language can make possible for him/her to expand the field of learning.